Quality of life in elderly patients with an ostomy – a study from the population‐based PROFILES registry. (2nd April 2018) - Verweij, N. M.; Bonhof, C. S.; Schiphorst, A. H. W.; Maas, H. A.; Mols, F.; Pronk, A.; Hamaker, M. E.
Abstract: Aim: Ostomies are being placed frequently in surgically treated elderly patients with colorectal cancer (CRC). An insight into the (potential) impact of ostomies on quality of life (QoL) could be useful in patient counselling as well as in the challenging shared treatment decision‐making. Method: Patients with CRC diagnosed between 2000 and 2009 and registered in the population‐based Eindhoven Cancer Registry received a QoL questionnaire (EORTC QLQ‐C30) in 2010. In addition, QoL was compared with an age‐ and sex‐matched normative population. Results: The study included 2299 CRC patients, of whom 494 had an ostomy. No differences were found in reported ostomy‐related problems between patients aged ≤65, 66–75 and ≥76 years. Ostomy patients aged 66–75 and ≥76 years reported significantly lower physical functioning compared with those without an ostomy. In the elderly (those aged ≥76 years) ostomates reported a worse physical and social functioning compared with the normative population. All these differences were of small clinical relevance. The impact of an ostomy seems to be more prominent in younger (≤75 years old) ostomates, as they experience more functional limitations and a decrease in global health status compared with younger nonostomy patients and the normative population. Conclusion: Although elderly (≥76 years old) patients with an ostomy report significantly more limitations in functioning compared with a normative population and elderly CRC patients without an ostomy, the clinical relevance of this finding is limited. In contrast, the impact of an ostomy is more prominent in younger patients. Thus, age itself is not a reason for withholding an ostomy.